2010
DOI: 10.1071/he10149
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Indigenous Games promoting physical activity and cultural connectedness in primary schools – Cluster Randomised Control Trial

Abstract: Further research specifically in terms of intensity and duration of TIG may inform whether physical activity may be improved. Enhancing the Indigenous cultural features of the existing TIG kit might positively influence Indigenous cultural connectedness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 4 publications
0
35
0
Order By: Relevance
“…One RCT (Nagel et al 2009), one cluster RCT (Kiran and Knights 2010) and two studies with non-randomised controls (Lee et al 1994;d'Espaignet et al 2003) were included. Other papers report case series or serial cross-sectional data.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…One RCT (Nagel et al 2009), one cluster RCT (Kiran and Knights 2010) and two studies with non-randomised controls (Lee et al 1994;d'Espaignet et al 2003) were included. Other papers report case series or serial cross-sectional data.…”
Section: Resultsmentioning
confidence: 99%
“…Only one included study (Kiran and Knights 2010) showed no improvements associated with activities described. The other 10 showed improvements in at least one measure and at one time point.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations